Genetic dissection of protein–protein interactions in multi-tRNA synthetase complex - Rho, Seung Bae (The National Academy of Sciences, 1999)
Cytoplasmic aminoacyl-tRNA synthetases of higher eukaryotes acquired extra peptides in the course of their evolution. It has been thought that these appendices are related to the occurrence of the multiprotein complex consisting of at least eight different tRNA synthetase polypeptides. This complex is believed to be a signature feature of metazoans. In this study, we used multiple sequence alignments to infer the locations of the peptide appendices from human cytoplasmic tRNA synthetases found in the multisynthetase complex. The selected peptide appendices ranged from 22 aa of aspartyl-tRNA synthetase to 267 aa of methionyl-tRNA synthetase. We then made genetic constructions to investigate interactions between all 64 combinations of these peptides that were individually fused to nonsynthetase test proteins. The analyses identified 11 (10 heterologous and 1 homologous) interactions. The six peptide-dependent interactions paralleled what had been detected by crosslinking methods applied to the isolated multisynthetase complex. Thus, small peptide appendices seem to link together different synthetases into a complex. In addition, five interacting pairs that had not been detected previously were suggested from the observed peptide-dependent complexes.